Asimilasi Yesus Kristus: Suatu Studi Analisis Menurut Filipi 2: 6-8: Artikel - Rio Janto Pardede; Naek Tua Parlindungan Hutagaol; Samuel Manaransyah (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
This study aims to analyze the assimilation of Jesus Christ according to Philippians 2: 6-8. The research method used is content analysis. The results showed that the assimilation of Jesus Christ showed that Jesus did not exercise His rights as God to defend His humanity. Based on content analysis research, it was found that the assimilation of Jesus Christ was different from humans (prisoner assimilation). Human rights are strongly fought for by the state or government, there is even a law that regulates to protect human rights while the rights of Jesus Christ as a human being are not protected by the state or government. In researching content analysis on the text of Philippians 2: 6-8, Biblical Theology views the assimilation of Jesus Christ divided into 5 components, namely: a) Jesus did not hold fast to His rights as God (2:6), b) Jesus put aside the glory of God. Him (2:7a), c) Jesus took on the nature of a human servant (2:7b), d) Jesus humbled Himself (2:8a), e) Jesus became obedient and died on the cross (2:8b).